Pengaruh Work Family Conflict terhadap Turnover Intention pada Dosen Wanita di Kota Bandung - Radityo Satya Wicaksana; Anna Rozana (Bandung Conference Series: Psychology Science, 2024)
Abstract. Female lecturers are faced with various challenges and demands in the workplace.The scope of lecturers' duties in the teaching aspect is quite varied, starting from designing teaching syllabi according to class characteristics and different student characteristics, providing teaching, as well as compiling and evaluating student assignments, these demands are carried out simultaneously with taking care of the family which can cause conflict, especially for female lecturers. who plays a dual role as a mother and career woman. If work-family conflict is not handled, it can lead to turnover intention, namely someone's thoughts about leaving their current job. This research aims to examine the influence of Work Family Conflict on Turnover Intention among female lecturers in the city of Bandung. This research uses a quantitative causality approach with simple linear regression techniques and the subjects in this research were 355 people. The Work Family Conflict Scale measuring tool was compiled by Carlson, Kacmar, & William (2000) and has been adapted into Indonesian by Soca (2018) and the Turnover Intention measuring tool uses the Turnover Intention Scale based on the theory of Mobley, Horner, and Hollingsworth (1978) which consists of three aspects and was modified from the turnover intention scale of Yin-Fah (2010) and has been adapted into Indonesian by Gevia (2020). Apart from that, the coefficient of determination test shows an R-Square value of 0.463, so it can be said that the Work Family Conflict variable has a contribution of 46.3% to Turnover Intention, so it can be concluded that Work Family Conflict has a significant effect on Turnover Intention, the rest is influenced by other variables not examined in this research. Abstrak. Dosen wanita dihadapkan dengan berbagai tantangan dan tuntutan di tempat kerja.Cakupan tugas dosen dalam aspek pengajaran cukup bervariasi, dimulai merancang silabus pengajaran sesuai dengan karakteristik kelas dan karakteristik mahasiswa yang berbeda ,memberikan pengajaran, serta menyusun dan mengevaluasi tugas mahasiswa, tuntutan tersebut dilakukan secara bersamaan dengan mengurus keluarga yang mana dapat menimbulkan konflik terutama pada dosen wanita yang menjalani peran ganda sebagai ibu dan wanita karier. Work-family conflict yang dialami apabila tidak ditangani dapat mengarah ke turnover intention yaitu pemikiran seseorang untuk keluar dari pekerjaannya sekarang. Penelitian ini bertujuan untuk menguji pengaruh Work Family Conflict terhadap Turnover Intention pada dosen wanita di kota Bandung. Penelitian ini menggunakan pendekatan kuantitatif kausalitas dengan teknik regresi linier sederhana dan subjek pada penelitian ini berjumlah 355 orang. Alat ukur Work Family Conflict Scale yang disusun oleh Carlson, Kacmar, & William (2000) dan telah diadaptasi ke dalam Bahasa Indonesia oleh Soca (2018) dan alat ukur Turnover Intention menggunakan dari Skala intensi turnover disusun berdasarkan teori dari Mobley, Horner, dan Hollingsworth (1978) yang terdiri dari tiga aspek dan dimodifikasi dari skala intensi turnover Yin-Fah (2010) dan telah diadaptasi ke dalam Bahasa Indonesia oleh Gevia (2020). Selain itu pada uji koefisien determinasi menunjukkan nilai R-Square 0,463 sehingga dapat dikatakan bahwa variable Work Family Conflict memiliki kontribusi sebesar 46.3% pada Turnover Intention, sehingga dapat disimpulkan bahwa Work Family Conflict berpengaruh signifikan terhadap Turnover Intention,sisanya dipengaruhi variable lain yang tidak diteliti dalam penelitian ini.